St. Vincent and the Grenadines : 2005 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2006)
Despite the impact of Hurricane Ivan, the economic activity of St. Vincent and the Grenadines has strengthened. Executive Directors welcomed the developments and the tax policy aimed to broaden the tax base and reduce concessions. They appreciated the home-grown Interim Poverty Reduction Strategy Paper aimed for reducing poverty. They urged to strengthen financial sector supervision and advised to seek greater regional cooperation. They also emphasized the need to accelerate growth, structural reforms, and reduce poverty, while restoring fiscal and external viability and reducing the debt.